Collaborative Learning, Reflective Practices and Psychological Resilience of Low - Performing ESL Learners in a Philippine Local College - Alenain, Donna; Lingon, Hazel; Javinar, Jay-Cee; Gordevilla, Marietess; Abustan, Arcangel Joshua; Galicia, Leomar (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined collaborative learning, reflective practices, and psychological resilience among low-performing English as a Second Language learners at a selected local college in Cavite. It was anchored in Zimmerman’s Self-Regulated Learning Theory and Vygotsky’s Sociocultural Theory, which explain how learners develop through self-monitoring, reflection, social interaction, scaffolding, and peer support. A quantitative, descriptive-correlational research design was employed. Respondents were purposively selected undergraduate ESL learners with English grades ranging from 75 to 81. Data were collected using a validated 47-item questionnaire covering collaborative learning, practical, cognitive, affective, and metacognitive reflection, and psychological resilience. Weighted mean, standard deviation, Pearson’s product-moment correlation, the Shapiro-Wilk test, scatterplot inspection, and outlier analysis were used. The respondents demonstrated a very high level of collaborative learning (M = 4.28, SD = 0.389), a very high overall level of reflective practices (M = 4.07, SD = 0.518), and a high level of psychological resilience (M = 4.06, SD = 0.536). Collaborative learning had a weak, positive, but non-significant relationship with reflective practices (r = .232, p = .217). However, collaborative learning was moderately and significantly related to psychological resilience (r = .480, p = .007). Reflective practices were also significantly associated with psychological resilience, with affective and metacognitive reflection showing the strongest relationships. The study concluded that collaboration and reflection function as distinct but complementary learning approaches that may strengthen learners’ resilience. It recommended integrating structured collaborative activities with journaling, guided reflection, self-evaluation, and targeted support for emotional regulation and proactive coping. The study supports SDG 4 on Quality Education, SDG 3 on Good Health and Well-Being, and SDG 8 on Decent Work and Economic Growth. Its sustainability impact lies in informing inclusive, evidence-based learner-support systems that promote academic persistence, emotional well-being, institutional responsiveness, and future employability.